No Evidence for a Relationship Between Hair Testosterone Concentrations and 2D:4D Ratio or Risk Taking - Ronay, Richard; van der Meij, Leander; Oostrom, Janneke K.; Pollet, Thomas V. (Frontiers in Behavioral Neuroscience, 2018)
Using a recently developed alternative assay procedure to measure hormone levels from hair samples, we examined the relationships between testosterone, cortisol, 2D:4D ratio, overconfidence, and risk taking. A total of 162 (53 male) participants provided a 3 cm sample of hair, a scanned image of their right and left hands from which we determined 2D:4D ratios, and completed measures of overconfidence and behavioral risk taking. While our sample size for males was less than ideal, our results revealed no evidence for a relationship between hair testosterone concentrations, 2D:4D ratios, and risk taking. No relationships with overconfidence emerged. Partially consistent with the Dual Hormone Hypothesis, we did find evidence for the interacting effect of testosterone and cortisol on risk taking but only in men. Hair testosterone concentrations were positively related to risk taking when levels of hair cortisol concentrations were low, in men. Our results lend support to the suggestion that endogenous testosterone and 2D:4D ratio are unrelated and might then exert diverging activating versus organizing effects on behavior. Comparing our results to those reported in the existing literature we speculate that behavioral correlates of testosterone such as direct effects on risk taking may be more sensitive to state-based fluctuations than baseline levels of testosterone.